2020
DOI: 10.1590/fst.32219
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, physicochemical, microbiological and sensory characterization of cow and buffalo ghee

Abstract: Three batches of each type of ghee were produced using 100 L of milk. Three samples of each batch, for a total of nine samples, were taken and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
3
6
2
1
Order By: Relevance
“…All these results can be accepted since the legal Egyptian Standards (ES: 154-5/2005) state that the iodine values for the extracted fat should be in the range of 26.4–43.1 g 100 g -1 . These results are not similar to those reported by another researcher who found that the iodine values of buffalo and cow ghee samples are 22.6 and 50.6 mg100 g -1 , respectively ( Pena-Serna and Restrepo-Betancur, 2020 ). It is considered that environmental conditions (such as temperature, origin, the composition of milk, processing condition, etc.)…”
Section: Resultscontrasting
confidence: 97%
“…All these results can be accepted since the legal Egyptian Standards (ES: 154-5/2005) state that the iodine values for the extracted fat should be in the range of 26.4–43.1 g 100 g -1 . These results are not similar to those reported by another researcher who found that the iodine values of buffalo and cow ghee samples are 22.6 and 50.6 mg100 g -1 , respectively ( Pena-Serna and Restrepo-Betancur, 2020 ). It is considered that environmental conditions (such as temperature, origin, the composition of milk, processing condition, etc.)…”
Section: Resultscontrasting
confidence: 97%
“…The n ‐3/ n ‐6, AI and TI values of cow ghee were lower than the concentration reported by Pena‐Serna et al. [ 37 ] for cow ghee. Whereas, UFA/SFA ratio of AY ghee (0.48) was also lower than the ratio reported by Jing et al.…”
Section: Resultscontrasting
confidence: 74%
“…Söz konusu bileşiklerin Ghee'ye kremamsı, tatlı aroma ve koyu karamelize aromalarını verdiği tespit edilmiştir. Tereyağının ısıtılması ile inek ve manda sütünden üretilmiş Ghee örneklerinin karşılaştırıldığı bir çalışmada ise [56], her iki Ghee örneğinin de laktik-fermente, bütirik-peynirimsi, tatlı, ransit, pişmiş, ahır, kimyasal ve metalik aromalarla karakterize oldukları ve özellikle laktik-fermente aromanın manda sütünden üretilmiş Ghee'de daha yüksek olduğu belirlenmiştir. Tekstürel özellik bakımından inek sütünden yapılmış Ghee'nin daha fazla partiküllü yapı göstermesine manda sütünden üretilen Ghee'nin kumsu yapı skorları daha yüksek bulunmuştur.…”
Section: Ghee Yağıunclassified